Re-envisioning psychology : debating paradigmatic foundations - Bansal, Parul (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"This book studies the ideological nature of mainstream scientific psychology. It raises critical questions on dominant forms of psychological theorization and praxis based on their validity, social relevance and power privileges. The book critically interrogates scientific images of the mind, individual, gender, development, society and culture that mainstream psychology throws up. The issues taken up in this book revolve around the pivotal concerns of psychology's scientific basis, its dominant quantitative research methodology, the construction of 'individual' as the unit of analysis, the conceptualization of 'social', 'cultural', and 'gender' in relation to that, and the understanding of abnormality as is shaped by the discourses of medical science, individualism, and capitalism. Comprehensive and topical, the book will be useful to students, researchers, and teachers of psychology, applied psychology, social work, gender and women studies, and sociology. It will also be of interest to professional counsellors and psychotherapists. Comprehensive and topical, the book would be useful to the students, researchers, and teachers of psychology, applied psychology, social work, gender and women studies, and sociology. It will also be useful for professional counsellors and psychotherapists"--
Is Psychology a Science? -- Should Psychological research be only about numbers? -- What is 'social' about Social Psychology? -- Where is 'culture' in Psychology? -- How is 'gender' treated in Psychology? -- What is 'abnormal' in Clinical Psychology? -- How to rethink 'Child' and 'Development' in Psychology?
Keywords: Psychology; PSYCHOLOGY / History; PSYCHOLOGY / Education & Training; PSYCHOLOGY / Applied Psychology